2014
DOI: 10.1148/radiol.13130942
|View full text |Cite
|
Sign up to set email alerts
|

Improved Late Gadolinium Enhancement MR Imaging for Patients with Implanted Cardiac Devices

Abstract: Purpose:To propose and test a modified wideband late gadolinium enhancement (LGE) magnetic resonance (MR) imaging technique to overcome hyperintensity image artifacts caused by implanted cardiac devices. Materials and Methods:Written informed consent was obtained from all participants, and the HIPAA-compliant study protocol was approved by the institutional review board. Studies in phantoms and in a healthy volunteer were performed to test the hypothesis that the hyperintensity artifacts that are typically obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 121 publications
(73 citation statements)
references
References 25 publications
1
72
0
Order By: Relevance
“…7 In subjects with pacemakers or implantable cardioverter-defibrillators (ICDs), for which strict institutional safety procedures were followed, a wideband LGE sequence was used to minimize artifacts from the battery pack. 8 Biventricular volumes and function were measured using standard volumetric technique from the cine short-axis images. 9 Images were visually assessed for the presence and distribution of LGE areas for each LV myocardial segment using a standard 16-segment cardiac model 10 ; regions of elevated signal intensity had to be confirmed in 2 spatial orientations.…”
Section: Imaging Studiesmentioning
confidence: 99%
“…7 In subjects with pacemakers or implantable cardioverter-defibrillators (ICDs), for which strict institutional safety procedures were followed, a wideband LGE sequence was used to minimize artifacts from the battery pack. 8 Biventricular volumes and function were measured using standard volumetric technique from the cine short-axis images. 9 Images were visually assessed for the presence and distribution of LGE areas for each LV myocardial segment using a standard 16-segment cardiac model 10 ; regions of elevated signal intensity had to be confirmed in 2 spatial orientations.…”
Section: Imaging Studiesmentioning
confidence: 99%
“…A frequency scout acquisition has also been commonly used at 3.0T as a method to shift the SSFP dark band artifacts away from the region of interest 11 ; such an approach could also be useful in the context of patients with implanted devices at any field strength. The effectiveness of other relatively simple steps taken to reduce artifact, specifically for late gadolinium enhancement imaging, have been demonstrated by Rashid et al 12 They found that the resonant frequency at the heart can be shifted by as much as 6000 Hz when a device generator is implanted at a typical distance of 5 cm to 10 cm from the heart. The late gadolinium enhancement sequence is most typically an inversion recovery FGE acquisition, with the inversion recovery pulse used to create image contrast by nulling the signal from viable myocardium.…”
Section: See Article By Schwitter Et Almentioning
confidence: 99%
“…Artifactual myocardial hyperintensity on late gadolinium enhancement images may potentially mimic infarct or fibrosis when the resonant frequency offset caused by the metal of the device generator exceeds the bandwidth of the inversion pulse. Rashid et al 12 and Stevens et al 13 showed that by simply increasing the bandwidth of the inversion recovery pulse, the inversion became much more uniform in the face of local field inhomogeneities, and the artifact was reduced. A wideband inversion pulse was also shown to be successful in reducing artifacts in late gadolinium enhancement imaging of patients with ICDs scanned at 3.0T, 14 where the local susceptibility gradients surrounding a metallic implant are twice what they are at 1.5T.…”
Section: See Article By Schwitter Et Almentioning
confidence: 99%
“…In about 10% of the analyzed short-axis views, artifact was seen in an area where scar was also identified. Reduction of artifact is possible with altered imaging sequences 16,17 and may result in a higher diagnostic yield of cardiac MRI in patients with previously implanted devices.…”
Section: Mris In Patients With Implanted Icdsmentioning
confidence: 99%